Membangun Kesadaran Kesehatan Mental di Kalangan Remaja: Sosialisasi untuk Meningkatkan Keseimbangan Emosi dan Kepercayaan Diri di SMP Islam Al-Azhar 32 Padang - Novriandi, Dani; Mukhtar, Muhammad Ihsan; Astuti, Ria Maylani; Primananda, Rifania; Hanoselina, Yulia (Lembaga Yasin AlSys, 2025)
Adolescent mental health is an important aspect that is often overlooked, even though adolescence is a critical phase in emotional and social development. The mental health socialization conducted at SMP Islam Al-Azhar 32 Padang aims to enhance adolescents' understanding of the importance of maintaining mental balance amid academic and social pressures. This activity involves interactive material presentations on the scope of mental health, its influencing factors, stress management strategies, and ways to help friends experiencing mental health disorders. The results of the socialization show that students experienced a significant increase in their awareness of the importance of mental health. They became more capable of recognizing early symptoms of mental disorders and understanding the importance of seeking support from family, friends, or professionals. Positive responses from students and support from the school indicate that this activity successfully built awareness of the importance of mental health in everyday life.